ANALISIS PENGARUH PEMAHAMAN KETENTUAN DAN PRESEPSI WAJIB PAJAK TENTANG PERATURAN PEMERINTAH NOMER 46 TAHUN 2013 TERHADAP KEPATUHAN DALAM MELAKSANAKAN KETENTUAN PADA WAJIB PAJAK PELAKU USAHA MIKRO KECIL DAN MENENGAH DI KOTA YOGYAKARTA - Yunitha Tri Kartika; Andri Waskita Aji (Jurnal Akuntansi, 2015)
This study aims to determine the effect of the provisions of the understanding and perception of actors taxpayer Micro, Small and Medium Enterprises of the Government Regulation No. 46 of 2013 on tax compliance in implementing the provisions of Government Regulation No. 46 of 2013 in the city of Yogyakarta. Sampling in this study using a convenience sampling and questionnaire survey method with the data collection. Respondents were sampled in this study are the individual taxpayers and corporate taxpayers in the city of Yogyakarta. Research data analysis using multiple linear regression with SPSS 17.0. Based on the results of the analysis conducted this study indicate that understanding the taxpayer on Government Regulation No. 46 of 2013 significantly influence taxpayer compliance in implementing the provisions of Government Regulation No. 46 of 2013. While variable taxpayer's perception of Government Regulation No. 46 of 2013 has no effect significantly on tax compliance in implementing the provisions of Government Regulation No. 46 of 2013. Keywords: provision understanding and perception of the taxpayer on government regulation number 46 of 2013.